ESSENTIAL OIL COMPOSITION AND ANTIOXIDANT, ANTICANCER ACTIVITIES OF ARTEMISIA FRIGIDA WILLD. GROWN IN MONGOLIA - Jambal, Irekhbayar; Ayurzana, Amarjargal; Shatar, Altantsetseg (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2023)
Medicinal plants have always been considered a healthy source of life for all people. In Mongolia, the use of various medicinal and food plants has a long history. In recent years, interest in plant-derived food additives has grown. This study was designed to determine essential oil chemical composition and evaluate antioxidant, cytotoxic activities of aerial parts serial fractions from Artemisia frigida Willd. grown in Mongolia. The chemical composition of essential oil from A.frigida Willd. was determined by GC-MS analysis. Among them 40 components (35.07%), 1,8-cineol (27.22%), borneol (3.01%), terpin-4-ol (4.51%), γ-cadinene (7.5%), α-terpineol (2.98%), bornylacetate (1.80%) were found to be the major ones. The ethanol crude extract of A.frigida Willd. was suspended in water and consequently fractionated with n-hexane, chloroform, ethyl acetate and butyl alcohol. All the fractions were examined for their antioxidant and cytotoxic activities by using DPPH and MTT assays, respectively. Ethyl acetate fraction showed the highest DPPH radical scavenging activity at a concentration of 50 µg/ml by 93.17% with the IC50 value of 11.68 µg/ml. MTT results showed that water fraction demonstrated significant cytotoxicity against A549 - human alveolar basal epithelial cell line, with values of 78.69 and 60.98% (50; 10 µg/ml; at 48 h). These suggest that the fractions of A.frigida Willd. could hold a good potential for use in the pharmaceutical industry.